PENGARUH PENERAPAN E-FILLING DAN E-BILLING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - FEBRINA, RIA; SARI, SARI; SUSANTI, NOVRIANI (JURNAL AKUNTANSI DAN KEUANGAN, 2024)
This study aims to determine the effect of the implementation of e-Filling and e-Billing on individual taxpayer compliance. The object of this research is 5222 individual taxpayers with 373 respondents obtained from the slovin formula. The data analysis technique used is descriptive statistical technique using primary data. This study uses a purposive sampling method with the characteristics of individual taxpayers who report SPT using e-filing and individual taxpayers who pay taxes using e-billing. Based on the results of the research conducted, it can be seen that partially the application of e-Filling and e-Billing together has an effect on individual taxpayer compliance. Simultaneously, it can be explained that the effect of implementing e-Filling and e-Billing on individual taxpayer compliance based on the coefficient of determination test shows the R square value of 40.9% while the remaining 59.1% is influenced by other variables not included in the study. this